Consider the expression 2√ 3 cos(x)csc(x)+4cos(x)-3csc(x)-2 √ 3 This expression can be represented as the product of the factors
...
1 answer:
The answer:
let be A(x) =<span>2√ 3 cos(x)csc(x)+4cos(x)-3csc(x)-2 √ 3
this function can be represented as </span><span>the product of the factors
proof
</span>2√ 3 cos(x)csc(x)+4cos(x)-3csc(x)-2 √ 3 =
2√ 3 cos(x)csc(x)+4cos(x)csc(x) / csc(x) - 3csc(x)- 2 √ 3 csc(x) / csc(x)
this method doesn't change nothing inside the function A(x)
so we have
[ 2√ 3 cos(x) +4cos(x) / csc(x) - 3 - 2 √ 3 / csc(x) ] . csc(x) this is a product of two factors,
[ 2√ 3 cos(x) +4cos(x) / csc(x) - 3 - 2 √ 3 / csc(x) ] and csc(x)
for more explanation
A(x) =[ 2√ 3 cos(x) - 3 + (4cos(x) - 2 √ 3 ) / csc(x) ] . csc(x)
You might be interested in
Answer:
It will take 29 days to lay the track
After 18 days the crew still has 77 miles of track left to lay
Step-by-step explanation:
203÷7
=29 days
L= 203 - 7(18)
L= 203 - 126
L= 77
True
False
False
True
False
False
Answer:
Step-by-step explanation:
(r/s)(x) is the quotien of r(x) = 3x - 1 and s(x) = 2x + 1:
r 3x - 1
(-----)(x) = ----------
s 2x + 1
Answer: 12 cakes
Step-by-step explanation:
Answer:
the median is 43
Step-by-step explanation: